KINERJA ARGININ SEBAGAI INHIBITOR KOROSI BAJA SS-304 DALAM LARUTAN HCL - Kayadoe, Victor; Kayadoe, Rita; Sunarti, Sunarti (Molluca Journal of Chemistry Education (MJoCE), 2018)
The Research has been conducted to study the corrosion inhibition of SS-304 in HCl solution using arginine on pickling process by weight loss methods. The Research carried out by variation of arginine concentration and temperature to determine its effect on inhibition efficiency and corrosion rate of SS-304. The results showed that the inhibition efficiency increases with increasing inhibitor concentration. Optimum inhibition efficiency was obtained at 0.0125 M (56.40 %), with corrosion rate of 1,18 mmy-1. In contrast, higher temperatures result in decreased inhibition efficiency up to 14.62 % at temperature of 55oC, with corrosion rate of 12,18 mmy-1.